Hubungan antara Kadar Feritin dengan Malondialdehyde pada Pasien Talasemia β Mayor di RSD dr. Soebandi Jember - Trinita Diyah Permatasari; Rini Riyanti; Desie Dwi Wisudanti (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Repeated blood transfusions, increased iron absorption, and ineffective erythropoiesis in major β thalassemia patients lead to iron overload characterized by elevated ferritin levels. Free iron will catalyze reactive oxygen species (ROS) formation by Fenton reaction that cause oxidative stress. Malondialdehyde (MDA) is the lipid peroxidation end product used to measure the oxidative stress. This study aimed to determine the correlation between ferritin levels and MDA levels in major β thalassemia patients at dr. Soebandi Hospital Jember. An analitic observational study with cross sectional study design which the subjects were 15 patients with major β thalassemia in the Pediatric Department at dr. Soebandi Hospital Jember who met inclusion and exclusion criteria. Ferritin levels measured by Enzyme-Linked Fluorescent Immuno Assay (ELFA) method and MDA levels measured by Thiobarbituric Acid Reactive Substances (TBARS) method using spectrophotometer at 535 nm. Data was analyzed with Shapiro Wilk normality test and Pearson correlation test. The mean of ferritin levels was 3540,46±3925,37 ng/mL and MDA levels was 4,77±2,03 nmol/mL. The result showed that there is strong positive correlation between ferritin levels and MDA levels with p value=0,001 and r=0,786 in major β thalassemia patients at dr. Soebandi Hospital Jember.